Optimizing irrigation for boosting Gynura Procumbens growth in Malaysia urban area - Abdul Salim, Nooryani; Hanafi, Marsyita; Shafie, Siti Mariam; Mashohor, Syamsiah; Hashim, Norhashila (Intelektual Pustaka, 2022)
Growing herbs traditionally could not meet the increasing demand for high medicinal value herbs in the pharmaceutical industry and domestic market. One of the solutions is by growing herbs using vertical structures in urban areas. Even so, the amount of water needed to optimise the growth of Asian local perennial herbs in vertical structures is yet to be explored. Hence, this paper investigated the performance of a fuzzy based irrigation method in optimising irrigation for boosting the local perennial herb growth. The understudy local perennial herb is Gynura Procumbens. The decision-making for irrigation relies on the data given by soil moisture, temperature, and humidity sensors. The performance of the proposed system is compared with a timer-based system, in terms of plant growth rates, given by average leaves diameter, height, and plant crown of local perennial herbs. The results have shown that the proposed intelligent irrigation system has reduced water consumption by 16.93% and the average plant growth rate has increased by at least 1.5% and to a maximum rate of 76.64%.